O moralmente possível e a semântica de termos modais na filosofia do direito de Kant - André Luiz Batiston (2019)
In the Metaphysical First Principles of the Doctrine of Right Kant uses the modal term "possible" in a particular sense that still needs to be elucidated. As observed in his doctrine of right, the philosopher employs the modal concept of possibility in main theses of private and public rights, asserting, for example, that "it is possible for me to have any external object of my choice as mine", or there is "the possibility of connecting a universal reciprocal coercion with the freedom of everyone", or that "any piece of land can be acquired originally". The aim of this dissertation is show that Kant uses the modal term “possible” in a specifically practical or moral sense, which is employed in precise sense of what is morally possible to do, i. e, what is "permitted" or "permissible" in face of practical reason. This way, the author would be making use a certain practical semantics of modal terms, where the notion of "morally possible" is connected to the idea that right, before being an obligation, is conceived as an authorization. It will be shown that this semantics, which employs the modal concept of possibility in a practical or moral sense, had already been developed in Kant's terminological and conceptual sources. This development is originally observed in notes of Leibniz, first philosopher to employ typical elements of modal logic in a practical sphere, and then in Baumgarten, an adept of the leibniz-wolffian matrix school that introduces the copious leibnizian idea that "possible" can be used, in relation to freedom, as "permissible". This unfolding would be at the starting point of what is understood today by deontic logic: that logic of norms developed in the mid-twentieth century, where "Permitted" and "Obligatory" deontic modal operators are employed in logical propositions such as "Possible" and "Necessary" alethics modal operators.